Assessing 12th Grade Students’ Critical Thinking on Atomic Structure Using Complex Multiple-Choice Test - Apriani Katili, Yeyen; A.R. Laliyo, Lukman; Lukum, Astin; Pikoli, Masrid; La Kilo, Akram (International Journal of Education, Vocational and Social Science, 2026)
This study aimed to assess the critical thinking abilities of 12th grade students on the topic of atomic structure using a complex multiple-choice test instrument based on the Rasch Model. The research found that the instrument was valid and reliable in measuring students' critical thinking skills. The majority of students (75%) demonstrated adequate critical thinking abilities, while 25% faced difficulties, particularly with items measuring inference and explanation. Students performed better on questions related to interpretation and evaluation but struggled with questions that required them to draw conclusions and explain more complex scientific phenomena. These results indicated that while students had a solid understanding of the basic concepts of atomic structure, they needed more practice to improve their higher-order critical thinking skills. Small gender differences were observed, with male students performing slightly better on analysis and inference items, although these differences were not significant. Overall, the findings suggest that while students had a strong foundational knowledge, there is a need for reinforcement through more challenging questions and deeper critical thinking exercises to further develop their critical thinking abilities.